Revisiting detachment techniques in human-biting ticks - GARGILI KELEŞ, AYŞEN (MOSBY-ELSEVIER, 2016)
Background: Early and complete removal of ticks using the right technique is important to reduce tick-transmitted diseases. Several chemical and mechanical detachment techniques have been described previously. Objective: We aimed to compare the performance of 4 tick-detachment techniques that are widely used in human beings and to determine the optimal method from these techniques. Methods: A cross-sectional study was conducted on 160 patients between April and June 2010. Patients with reported tick bite were reviewed retrospectively and divided into the following 4 groups according to the tick-detachment technique used: card detachment, lassoing, freezing, and tweezers. Performance of each technique was evaluated according to the number of fully detached, nondetached, and crushed ticks and the duration of application. Results: Of the 160 tick-bite cases assessed, we found the following efficacy rates: 82.5% (33/40), technique using tweezers; 47.5% (19/40), lassoing technique; 7.5% (3/40), card detachment; and 0% (0/40), freezing technique. The efficacy rate of the technique using tweezers was significantly higher than that of the other 3 techniques (P < .05). Limitations: This was a relatively small sample size and not designed as a randomized clinical trial. Conclusion: Tick detachment using tweezers, performed in an appropriate manner, is the easiest and most effective technique.
Keywords: freezing; parasite-host relations; techniques; tick bites; tick infestations; tweezers; REMOVAL; TRANSMISSION; ATTACHMENT; DURATION